An Engineering-Problem-Based Short Experiment Project on Finite Element Method for Undergraduate Students - Yanjie Guo; Lijuan Yang; Xuefeng Chen; Lei Yang (MDPI AG, 2020)
How to cultivate students’ engineering practice ability in the digital manufacturing period is a difficult problem. This paper presents a finite element analysis experiment project for undergraduate students. The goals of implementing finite element modeling in this project are to enhance students’ understanding of theoretical mechanics and to introduce computational methods to undergraduate students at an early stage during their undergraduate education. The students are required to use different methods to analyze the stress state of a typical engineering structure and seek the optimal design. Then, the experiment score is divided into two parts according to the course objectives. We analyzed the score distribution to find the limitations of teaching. The feedback from the students demonstrate that the experiment case from the engineering project can increase their interest in learning and applying the acquired knowledge. After comparisons, our conclusion is that outcome-based education (OBE) can effectively improve the quality of classroom teaching, and this experimental project can improve students’ engineering practice ability and obtain satisfactory teaching results.